Serological Diagnosis of Autoimmune Bullous Skin Diseases - Saschenbrecker, Sandra; Karl, Ingolf; Komorowski, Lars; Probst, Christian; Dähnrich, Cornelia; Fechner, Kai; Stöcker, Winfried; Schlumberger, Wolfgang (Frontiers in Immunology, 2019)
Autoimmune bullous dermatoses encompass a variety of organ-specific autoimmune diseases that manifest with cutaneous and/or mucosal blisters and erosions. They are characterized by autoantibodies targeting structural proteins of the skin, which are responsible for the intercellular contact between epidermal keratinocytes and for adhesion of the basal keratinocytes to the dermis. The autoantibodies disrupt the adhesive functions, leading to splitting and blister formation. In pemphigus diseases, blisters form intraepidermally, whereas in all other disease types they occur subepidermally. Early identification of autoimmune bullous dermatoses is crucial for both treatment and prognosis, particularly as regards tumor-associated disease entities. The diagnosis is based on clinical symptoms, histopathology, direct immunofluorescence to detect antibody/complement deposits, and the determination of circulating autoantibodies. The identification of various target antigens has paved the way for the recent development of numerous specific autoantibody tests. In particular, optimized designer antigens and multiplex test formats for indirect immunofluorescence and ELISA have enhanced and refined the laboratory analysis, enabling highly efficient serodiagnosis and follow-up. This review elaborates on the current standards in the serological diagnostics for autoimmune bullous dermatoses.